PVDFBaTiO3/carbon nanotubes ternary nanocomposites: Effect of nanofillers and processing. Issue 2 (13th May 2015) - Sanchez, Freddy A.; González‐Benito, Javier
Abstract : Ternary thermoplastic systems based on poly(vinylidene fluoride), PVDF, filled with barium titanate, BaTiO3, submicrometric particles and carbon nanotubes, CNT, were prepared. Their structure and morphology were studied as a function of composition and finally correlated with thermal and mechanical properties. High energy ball milling, HEBM, under cryogenic conditions and subsequent hot pressing were used to obtain films with quite uniform dispersion of the nanofillers. The presence of BaTiO3 particles and CNT did not modify the thermodegradation mechanism of the PVDF. However, enough amount of BaTiO3 seemed to inhibit the volatility of the products of pyrolysis, hindering the decomposition of PVDF. The presence of CNT favored the PVDF thermodegradation probably due to improved heat transmission by an increase in the thermal conductivity. Variations in PVDF thermal transitions were more dependent of processing conditions. Improvements in the mechanical properties of PVDF were ascribed to a reinforcing effect of the fillers. This effect only happened below the fraction of percolation of CNT, pointing out that CNT reinforce through an optimum load transfer from the PVDF matrix to the nanofillers. POLYM. COMPOS., 38:227–235, 2017. © 2015 Society of Plastics Engineers